"Conspiracy Theories" and The Corona: Paranoia, Populism, Soft power, Cultural Authority and "fragmented journalism": - AlQahtani, Saud Rubaya Mousa (Journal of Risk and Crisis Management, 2022)
The Coronavirus is one of the most severe epidemics historically, which has many effects with the spread of conspiracy theories, fake news, and misinformation about it. This article describes the conspiracy as a complex cultural symptoms, that frames political and social conflict, it is associated with paranoia, populism, soft power, social fabric, authority, cognitive instability, and includes the idea of creating or resisting a "new society". It also argues that Conspiracy narratives about the pandemic are repetitive and contradictory, and digital platforms, search engines, and the film industry have promoted and profited from them; which was reflected negatively on the attitudes and behavior. There is also a "utopian" link between media and technical pragmatism, and the political and scientific agenda; it has resulted in a "fragmented journalism", that advance post-truth policies, it aims at the fragmentation, politically polarization, and excitement of the audience, it highlights ideological disparities and extremism of opinions; and fuels mistrust of the governments and its institutions. Then it presents some suggestions that would work to expose and distort the conspiratorial discourse and mitigate its impact.
Keywords: Conspiracy theory; coronavirus; fragmented journalism; Paranoia; Populism; Soft power